IMMU-10. CENTRAL NERVOUS SYSTEM NEUROBLASTOMA METASTASES PSEUDOPROGRESSION FOLLOWING INTRAVENTRICULAR ANTI-B7H3 RADIOIMMUNOTHERAPY. (23rd April 2019) - Kramer, Kim; Khan, Osman; Haque, Sofia
Abstract: BACKGROUND: While immunotherapy has revolutionized the treatment for several solid tumors, pseudoprogression, radiographically defined as the initial increase in tumor volume followed by tumor shrinkage, is less clearly defined. This is particularly noteworthy for patients with central nervous system metastases, commonly seen in patients with advanced melanoma or non-small cell lung cancer treated with PD-1 or CTLA-4 inhibitors. B7-H3 (CD276) is a transmembrane protein belonging to the B7 family of costimulatory molecules. 1 Several solid tumors overexpress B7-H3, and expression appears to be closely associated with immune escape, tumor cell invasion and metastases. The incidence of pseudoprogression after B7-H3 therapy is unknown. METHOD: A 4 year old girl with central nervous system metastases of neuroblastoma underwent resection of 2 left parietal lobe lesions, the largest 1.4 cm with edema, enhancement and restricted diffusion, followed by craniospinal radiation therapy, irinotecan, temozolomide, inducing a second remission with expected MR appearance in the operative cavity. She was then registered to clinicaltrials.gov (NCT00089245) with intraventricular 131-I-anti B7-H3. One month after therapy, routine MR revealed increased nodular enhancement around both operative cavities with adjacent leptomeningeal enhancement, concerning for progressive neuroblastoma. The patient remained asymptomatic. RESULTS: A repeat brain performed 2 weeks later showed interval resolution of both the operative cavity and leptomeningeal enhancement and edema. Repeat brain and spine MR performed 6 months later shows continued remission with complete resolution of all enhancement and edema. RESULTS: Anti- B7-H3 therapy caused an immediate inflammatory reaction with spontaneous radiographic resolution and return to baseline 2 weeks later, all in the absence of concurrent steroid administration. CONCLUSION: Though the precise frequency and timeline is unclear, B7-H3 directed therapy may be added to the list of immunotherapeutic agents recognized to cause pseudoprogression. Key efforts are now being made to correlate the appearance of CNS neuroblastoma pseudoprogression with overall survival.